Improving Students’ Speaking Ability through Self-Recorded Video at Grade Vll SMP Negeri 1 Sipirok - Rahma Yulia; Rahmat Huda; Angga Octo; Arief Leo Pane; Annahari; Leli Purnama Nasution (CV. Alfa Pustaka, 2025)
This research aims to improve students' speaking ability through the use of self-recorded video tasks among Vll grade students of SMP Negeri 1 Sipirok. The sample consisted of 32 students, selected randomly. The method used in this study is Classroom Action Research (CAR) with a descriptive qualitative approach. The research was conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The instruments used include observation sheets and performance assessments based on five criteria: Grammar, Vocabulary, Comprehension, Fluency, and Pronunciation. The results showed an improvement in students’ speaking ability from the first to the second cycle. The average score of students in Cycle I was 67.31, which increased to 77.03 in Cycle II. This improvement was also supported by students’ more active participation in the speaking tasks. Therefore, the use of self-recorded video tasks is proven to be effective in enhancing students’ speaking ability